Electrical conductivity enhancement of alkaline earth titanates for high-temperature thermoelectric applications - Manon, Alexandre (2023)
With the global energy crisis, new methods and devices to decrease primary energy consumption are needed. In many sectors with unexploited exhausted heat where standard thermodynamic cycle such as the Rankine cycle cannot be used, the use of a thermoelectric generator can produce electricity from waste exhaust heat to increase the efficiency. The state-of-the-art n-type oxide thermoelectric materials are based on rare-earth doped strontium titanate (SrTiO3). Alkaline earth titanates have a similar electronic structure. It is then expected that doped barium titanate (BaTiO3) and calcium titanate (CaTiO3) are potential candidates for n-type oxide thermoelectric materials. These materials were the subject of numerous studies, however, studies to make them performant thermoelectric materials are rare. Electrical conductivity is one key parameter to achieve high thermoelectric performances. Reports of conductive barium titanate are scarce, and none of them reported sufficient electrical conductivity for thermoelectric applications. Reports of high electrical conductivity of rare-earth-doped calcium titanate are even fewer. Creating oxygen loss and donor doping (e.g., replacing one Sr3+ on the A-site with one La3+ in SrTiO3) are two common strategies to create electrons and achieve high electrical conductivity in metal oxides. These reactions are often energetically unfavourable. A high sintering temperature with a low oxygen partial pressure is typically needed to facilitate both oxygen loss and donor doping. Often sintering is conducted in a reducing atmosphere using a tube furnace with a limited maximum temperature (typically <1,600°C for conventional tube furnaces). In this project, a combination of arc melting and spark plasma sintering was specifically chosen to obtain high electrical conductivity of lanthanum-doped barium titanate and lanthanum-doped calcium titanate. These two techniques offer extremely high temperatures, high heating/cooling rates and low oxygen partial pressure. The electronic compensation mechanism via donor doping, in which the alkaline earth element is substituted by a lanthanum that increases the number of charge carriers by one electron, becomes favoured over the ionic compensation mechanism under such conditions, giving rise to high charge carrier concentration. Additional oxygen vacancies can be created, further increasing the electron concentrations by two electrons for each oxygen vacancy. Three families of compositions based on lanthanum-doped barium titanate and lanthanum-doped calcium titanate were synthesised and characterised. Two families of the compositions are designed according to the electronic compensation mechanism via lanthanum donor doping (general formula LaxBa1–xTiO3 and LaxCa1–xTiO3). In the third family of the compositions, the lanthanum doping in calcium titanate is charge-compensated by creation of calcium vacancies (general formula: LaxCa1–(3/2x)TiO3). X-ray diffraction revealed a complete solid solubility for both LaxBa1–xTiO3 and LaxCa1–xTiO3. Perovskite structures were observed for 0 ≤ x ≤ 1 with changes of lattice parameters following Vegard’s law. Compositional analysis using electron probe microanalysis (EPMA), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) showed the atomic ratios of the total A-site cations to the B-site cations (Ti) are close to the nominal ratio of 1:1 in both LaxBa1–xTiO3 and LaxCa1–xTiO3 systems. Inhomogeneous distribution of the two A-site cations (La and Ba in LaxBa1–xTiO3, La and Ca in LaxCa1–xTiO3) were observed in some compositions. For lanthanum-doped calcium titanate with A-site deficient doping mechanism (LaxCa1–1.5xTiO3), titanium-rich secondary phases were observed, suggesting this doping mechanism is not favoured under the used synthesis conditions. Exceptionally high electrical conductivity was achieved in all the three families of compositions. The three systems showed metallic behaviours from in all lanthanum-doped compositions. Electrical conductivity increased with the doping level (x) until the drop of the sinterability. For lanthanum-doped barium titanate, the composition of x=0.3 (La0.3Ba0.7TiO3) exhibited an electrical conductivity of 3,700 S.cm−1 at room temperature, which is the highest electrical conductivity achieved to date for this family of compositions. A high power factor of 0.6 mW.m−1.K−2 was obtained at 365 °C in the composition x=0.2 (La0.2Ba0.8TiO3). For lanthanum-doped calcium titanate with the electronic compensation mechanism, the composition x=0.5 (La0.5Ca0.5TiO3) showed a high electrical conductivity of 3,200 S.cm−1 at room temperature. The highest power factor of 0.97 mW.m−1 .K−2 was obtained at 270°C in the sample x=0.2 (La0.2Ca0.8TiO3) sintered at 1500°C, which is comparable to the highest power factor values reported in the literature that were obtained at much higher temperatures (∼740 °C). This project demonstrates the significant capability of arc melting and spark plasma sintering for boosting oxygen loss and donor doping to generate electrons and achieve exceptionally high electrical conductivity in metal oxides. This manufacture approach can be applied to fabricate a wide range of highly conductive n-type metal oxides.